ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH TABUNGAN TANDA 360 BANK OCBC NISP - Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
This research aims to get factual and conceptual information about "analysis of the influence of the quality of service to the satisfaction of the customer's Savings Bank OCBC NISP 360 Marks". The technique used is the technique of observation or survey using a questionnaire (questionnaire) towards Clients Savings Sign 360. A list created by using the Likert scale is structured. Samples taken as many as 100 respondents. The results of the survey and the results of the data processing is done with SPSS. 14.0 obtained research results of simultaneous service quality (tangible, reliability, responsiveness, assurance and emphaty) have a relatively strong contribution towards the satisfaction of the customer. Partially variable reliability has a pretty strong contribution towards the satisfaction of the customer with a positive prediction and happens significantly. The variable responsiveness has pretty strong contribution towards customer's satisfaction with the positive prediction and occurs on a si gnifican.